2019
DOI: 10.1177/2372732218818587
|View full text |Cite
|
Sign up to set email alerts
|

Decision Making and Alcohol: Health Policy Implications

Abstract: How people make decisions about alcohol can have implications for policy. Policies aimed at reducing alcohol-related harms need to take account of variability in individual decision making, and the impact of addiction and intoxication on choice behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Understanding these decision strategies can inform interventions to encourage the use of AID alternatives when people are already intoxicated. Specifically, our results suggest tailoring AID intervention approaches to the decision strategies individuals use while intoxicated (Davis-Stober et al, 2019). Individuals who employ a compensatory strategy (i.e., ride service cost sensitive) may benefit more from interventions focused on reducing the cost of AID alternatives, such as free or discounted safe ride programs promoted at bars or on ride service apps (Fell et al, 2020).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Understanding these decision strategies can inform interventions to encourage the use of AID alternatives when people are already intoxicated. Specifically, our results suggest tailoring AID intervention approaches to the decision strategies individuals use while intoxicated (Davis-Stober et al, 2019). Individuals who employ a compensatory strategy (i.e., ride service cost sensitive) may benefit more from interventions focused on reducing the cost of AID alternatives, such as free or discounted safe ride programs promoted at bars or on ride service apps (Fell et al, 2020).…”
Section: Discussionmentioning
confidence: 88%
“…Our results suggest the possibility of tailoring AID interventions to the decision strategies individuals use while intoxicated as an avenue for future research (Davis-Stober et al, 2019). Perski et al (2021) conducted a review of just-in-time interventions attempting to reduce substance-related behaviors (e.g., alcohol, nicotine, cannabis) and found mixed support for this type of intervention in reducing alcohol-related outcomes.…”
Section: Discussionmentioning
confidence: 94%
“…For example, individuals in a suicide crisis may not remember and consider all relevant choice information and may not generate effective solutions. Davis-Stober et al (2019) highlight the risky decision strategies of intoxicated individuals and show that some can benefit from simple mental rules or heuristic decision strategies. It may be that moral objections to suicide, combined with RC, may simplify the decision-making of religious suicidal young adults in a suicide crisis and provide a heuristic decision strategy, e.g., "A person committed to my beliefs does not take their life".…”
Section: Discussionmentioning
confidence: 99%
“…Davis-Stober et al ( 2019) examined the influence of decision making on alcohol consumption and its implications for health policies. They found that individuals with high levels of impulsivity and low conscientiousness are more likely to engage in excessive drinking, highlighting the need for targeted interventions that consider personality traits (Davis-Stober et al, 2019).…”
Section: E-issn: 3041-8542mentioning
confidence: 99%